Identification of factors responsible for the occurrence of cracks in cast iron pipe networks in sewage in Palmas-TO - Paz, Lidiane Andrade Fonseca da; Arrais, Kaique Ferreira; Correia, Sandra dos Santos Mendes; Lima, Diogo Pedreira; Denes, Alessandra Juliana; Fernandes, Fernando Antonio da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Cast irons are basically alloys of the Fe-C-Si ternary system containing carbon contents above 2%. The sewage pipes studied iron are arranged in Palmas-TO in Southern Master Plan. Although the cast iron pipes offer the advantages of price, rental locations in heavy traffic and little overlap in cases of the pipe to be deep seated above the load limits of other materials, in cases of apparent pipe, in cases of passage barriers, spans of bridges, rivers and structures subject to vibration and in cases of large slope. Even with all these advantages some of these tubes Palmas-TO showed cracks along the years. Some of these effects have tubes from corrosion and cracking. These cracks present in most cases at the side of the tube, where it has tube movement and larger voids of aggregates which were arranged in the pipe bedding, bedding and provisions of some sections of pipe mineral aggregate meets high grading of somehow contribute to cracks when handling the tubes. Even with these specific problems we look at the economic advantages and disadvantages of cast iron over other materials used in sanitation, and verified the company’s need to have their works on the cast iron pipes.